Catalyst free ethylene glycol promoted synthesis of spiro[indene-2, 2′-naphthalene]-4′-carbonitriles and spiro[naphthalene-2, 5′-pyrimidine]-4-carbonitriles via one-pot three-component reaction. Issue 52 (28th December 2016) - Khanna, Garima; Saluja, Pooja; Khurana, Jitender M.
Graphical abstract: Highlights: Catalyst free synthesis of spiro compounds has been described. Good yield of products. No use of chromatographic techniques for purification. Abstract: A facile and convenient procedure for the synthesis of spiro compounds has been described. The procedure involves the one-pot condensation of indane-1, 3-dione or 1.3-dimethylbarbituric acid, aromatic aldehydes and cyclohexylidene malononitrile in ethylene glycol at 100 °C in absence of any catalyst. The products were obtained in good yields without use of any chromatographic techniques.